Isolation and Molecular Characterization of Klebsiella And Enterobacter Species Recovered in Sunflower Seed Agar from Cases Resembling Respiratory Cryptococcosis - Felix Emele Emele; Kehinde Caleb Daramola; Arthur Ebelenna Anyabolu (Tropical Health and Medical Research, 2021)
Respiratory cryptococcosis caused by Cryptococcus species can present with symptoms indistinguishable from bacterial or viral etiology. Cryptococcus species produce typical colonial features on Sunflower Seed Agar (SSA), which aids in rapid diagnoses of cryptococcosis. In studying respiratory cryptococcosis, we observed bacterial growths on SSA that resembled Cryptococcus species in colonial characteristics. This study aimed at identifying and characterizing those bacterial isolates for documentation. Sputum samples were collected from 201 patients with symptoms suggestive of respiratory cryptococcosis. The samples were inoculated onto SSA, incubated at 37oC for two weeks. Suspected colonies were further evaluated. Of the samples, none yielded Cryptococcus species, although a total of twenty Cryptococcus-resembling bacterial colonies were encountered and isolated. Eight of the isolates could not amplify by PCR techniques. The other twelve were identified as follows: Klebsiella pneumonia (8 or 67%), Klebsiella ozaneae (3 or 25%), and Enterobacter ludwigii (1 or 8%). All isolates were susceptible to Ertapenem, Meropenem, and Fosfomycin but resistant to ampicillin. Results show that Klebsiella and Enterobacter pneumonia-like illnesses can be misidentified as cryptococcosis using SSA.  Reliance on microscopic rather than macroscopic, colonial features on SSA will prevent misdiagnosis.